Pembrolizumab versus the standard of care for relapsed and refractory classical Hodgkin's lymphoma progressing after brentuximab vedotin: an indirect treatment comparison. Issue 6 (3rd June 2018) - Keeping, Sam; Wu, Elise; Chan, Keith; Mojebi, Ali; Ferrante, Shannon Allen; Balakumaran, Arun
ABSTRACT: Background : There is significant unmet need among patients with relapsed and refractory classical Hodgkin's lymphoma (RRcHL) who have failed multiple lines of therapy, including brentuximab vedotin (BV). Pembrolizumab, an immune checkpoint inhibitor, is one possible treatment solution for this population. Research methods : The objective of this study was to compare progression-free survival (PFS) with standard of care (SOC) versus pembrolizumab in previously BV treated RRcHL patients. A systematic literature review identified one observational study of SOC that was suitable for comparison with KEYNOTE-087, the principal trial of pembrolizumab in this population. Both naïve and population-adjusted (using outcomes regression) pairwise indirect comparisons were conducted. The primary analysis included all patients who had failed BV, with a secondary analysis conducted including only those known to have failed BV that was part of definitive treatment. Results : In the primary analysis, SOC was inferior to pembrolizumab in both the unadjusted comparison (HR 5.00 [95% confidence interval (CI) 3.56–7.01]) and the adjusted comparison (HR 6.35 [95% CI 4.04–9.98]). These HRs increased to 5.16 (95% CI 3.61–7.38) and 6.56 (95% CI 4.01–10.72), respectively, in the secondary analysis. Conclusion : Pembrolizumab offers a significant improvement in PFS compared to SOC in this population.